Suppression in object-based attention. Issue 2 (7th February 2019) - Couperus, Jane W.
ABSTRACT: This study examines suppression in object-based attention in three experiments using an object-based attention task similar to Egly, R., Driver, J., & Rafal, R. D. (1994. Shifting visual attention between objects and locations: Evidence from normal and parietal lesion subjects. Journal of Experimental Psychology: General, 123(2), 161–177. doi:10.1037/0096-3445.123.2.161) with the addition of a distractor. In Experiment 1 participants identified a target object at one of four ends of two rectangles. The target location was validly cued on 72% of trials. The remaining 28% were located on the same or a different object. Sixty-eight percent of trials also included a distractor on one of the two objects. Experiment 1 failed to show suppression when a distractor was present, but did demonstrate the spread of attention across the attended object when no distractor was present. Experiment 2 added a mask to the paradigm to make the task more difficult and engage suppression. When suppression was engaged in the task, data showed suppression on the unattended (different) object, but not on the attended (same) object. Experiment 3 replicated findings from Experiment 1 and 2 using a within participants design. Findings are discussed in relation to the role of suppression in visual selective attention.